The Antibacterial Property of Nigella sativa (Black seed) Oil Against Gram-positive and Gramnegative Bacteria - Abdullah, Sakar Ahmed; M. Salih, Tara Faeq; Hama, Abdullah Ahmed; Ali, Salar Ibrahim; Hamaamin, Hassan Hussein (Kurdistan Journal of Applied Research, 2022)
Antimicrobial resistance is one of the most challenges ? that face the world today, and it is heading toward the post-antibiotic era. Traditionally, herbal extracts, medicinal plant oil extracts, and probiotics have been used as an alternative to antibiotics due to bacterial resistance and drug side effects. This ?work is carried out to evaluate the antimicrobial efficacy of Nigella sativa oil extracts ?against common resistant bacteria, including Methicillin-resistant staphylococcus aureus (MRSA) and Pseudomonas aeruginosa. The black seed was purchased from the traditional herbal medicine market, Hot extraction of the oil was performed. The bacteria were obtained from a microbiology company and from clinical samples at the Shar hospital in Sulaimani Provence. The bacteria were gram-negative (Salmonella enterica, Escherichia coli, and Pseudomonas aeruginosa) and gram-positive (methicillin-resistant Staphylococcus aureus (MRSA), Bacillus subtilis, and Bacillus cereus). The agar ?diffusion well technique and minimum inhibitory concentration (MIC) were used. The black seed oil components were analyzed by the Gas Chromatograph mass spectrum. The results revealed that the oil of Nigella sativa shows a ?significant effect on Gram-positive bacteria, including MRSA, which is known as a multidrug resistance bacterium. ? Bacillus subtilis was more sensitive than other strains, and the significant antibacterial effect of the extracted was observed against Escherichia coil, while it has no significant effect on Pseudomonas aeruginosa and Salmonella enterica.? Determination of Nigella sativa oil minimum inhibitory concentration (MIC) for Gram-positive bacteria is 100 ml for Staphylococcus aureus and Bacillus subtilis, and the MIC was 200 ml and 400 ml for Bacillus cereus and MRSA respectively. This study concludes that oil extract of Nigella sativa is a ?good natural antimicrobial, it can be used against ?MRSA and other Gram-positive bacteria.